Rancang Bangun Alat Ukur Konduktivitas Panas Bahan Dengan Metode Needle Probe Berbasis Mikrokontroler AT89S52 - Syaefullah, Rakhmat; Yulianto, Gatot; Suryono, Suryono (BERKALA FISIKA, 2006)
A device for measuring thermal conductivity of homogen materials using a Needle Probe method has been designed. This method uses a metal rod which emited a heat stream and a temperature sensor placed in the middle of interior heater at probe to measure changes in temperature inside the probe. This measuring instrument represent development digitally from measuring instrument which have been made with analog system. With AT89S52 microcontroller application as data processor bases, temperature detected can be presented by sevent segment which have been controlled by BCD converter. Basically thermal conductivity measuring instrument with this Needle Probe method represent a digitally thermal detecting system which attached at Needle Probe. Every increase 1 0C, the temperature censor give output equal to 0.01 V with correctness of displayed equal to 1 0C and error point level equal to 0.01 %. Key word: Needle Probe method, ADC, AT89S52 microcontroller, seven segment.